The Relationship Between the Family Environment and the Role of Friends with Drug Abuse re-Abuse at the Pamardi Putra Social Rehabilitation Center, Lembang, West Bandung Regency - Fikri Ardiansyah; Ahmad Zaelani (Universitas Ibn Khaldun Bogor, 2023)
According to data in the Pamardi Putra Social Rehabilitation Lembang, the number of rehabilitated former drug users from May - July 2023 has fluctuated. The problem that often occurs is the tendency of former drug users to have difficulty avoiding their desire to stop using drugs. A preliminary study of the 10 respondents, shows that 7 people use drugs back due to the influence of friends, 2 people think using drugs can eliminate the problems in the family, and one person feels more confident when using the drug. The purpose of this study was to determine the correlations between family environment and the role of friends' social environment with repeated drug abuse. The method used is correlative analytics with the cross-sectional approach. The research population is 49 people and samples taken by total sampling technique are 62 people. Data obtained through questionnaires were analyzed through univariate tests and bivariate (chi-square). The results were obtained by respondents who experienced repeated drug abuse of 14 people (28,6%), respondents with a negative family environment of 25 people (51%), and respondents with the role of friends of 20 people (40,8%). There is no relationship between family environment with repeated drug abuse (p-value = 1), and there is no relationship role of friends with repeated drug abuse (p-value = 0.002). It is recommended that Pamardi Putra Rehabilitation Center Lembang consider making a counseling program for the former drug users to be aware of the various kinds of negative influences and can choose to get along with a good friend to avoid the repeated of drug abuse stemming from the influence of peers.